An oral history of medical laboratory development in francophone West African countries - Winny Koster; Albert G. Ndione; Mourfou Adama; Ibrehima Guindo; Iyane Sow; Souleymane Diallo; Jean Sakandé; Pascale Ondoa (AOSIS, 2021)
Background: Underdeveloped and underused medical laboratories in sub-Saharan Africa negatively affect the diagnosis and appropriate treatment of ailments. Objective: We identified political, disease-related and socio-economic factors that have shaped the laboratory sector in Senegal, Mali and Burkina Faso to inform laboratory-strengthening programmes. Methods: We searched peer-reviewed and grey literature from February 2015 to December 2018 on laboratory and health systems development from colonial times to the present and conducted in-depth interviews with 73 key informants involved in (inter)national health or laboratory policy, organisation, practice or training. This article depended on the key informants' accounts due to the paucity of literature on laboratory development in francophone West African countries. Literature and interview findings were triangulated and are presented chronologically. Results: Until around 1990 there were a few disease-specific research laboratories; only the larger hospitals and district health facilities housed a rudimentary laboratory. The 1990s brought the advent of donor-dictated, vertical, endemic and epidemic disease programmes and laboratories. Despite decentralising from the national level to the regional and district levels, these vertical laboratory programmes biased national health resource allocation deleteriously neglecting the development of the horizontal, general-health laboratory. After the year 2000, the general-health laboratory system received more attention when, influenced by the World Health Organization, national networks and (sub-)directorates of laboratories were installed. Conclusion: To advance national general healthcare, as opposed to disease-specific healthcare, national laboratory directors and experts in general laboratory development should be consulted when national policies are made with potential laboratory donors.